(untitled) (Journal on Excellence in College Teaching, 2024)
This year, as we celebrate 40 years of faculty learning communities and 10 years of the Learning Communities Journal, we recognize the broad expansion of learning communities from their initial focus, which we will call traditional, to new and unforeseen structures, venues, pathways, and outcomes, often at extremes beyond our original expectations. In this issue we explore some of these extremes.